PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BENGKEL WARNA INDAH SPECIALIST LAS DAN CAT MOBIL KEDIRI - Kristiantoro Priyo Widodo; Udik Jatmiko; Suseno Hendratmoko (Cahaya Ilmu Bangsa, 2024)
This research aims to determine the influence of work motivation and work discipline on employee performance at the Color Indah Workshop, a car welding and paint specialist in Kediri. The variables in this research are Work Motivation (X1), Work Discipline (X2), and Employee Performance (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. Meanwhile, the analysis used is validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and coefficient of determination. Sampling in this study used purposive sampling taking into account all employees of Bengkel Warna Indah, a Kediri car welding and paint specialist, totaling 31 people based on the results of the research conducted. The results of this research using the SPSS 25.0 program using a significance level of 5% or 0.05 with results (1) partially work motivation has a significant effect on employee performance with a significant value of 0.039 < 0.05, which means H1 is accepted and Ho1 is rejected. (2) partially work discipline has a significant effect on employee performance with a significant value of 0.000 <0.05, which means H2 is accepted and Ho2 is rejected. (3) simultaneously work motivation and work discipline have a significant effect on employee performance with a significant value of 0.000 < 0.05, which means Ha3 is accepted and Ho3 is rejected.